Lapin rajat ja murrerajat - Mantila, Harri (Kotikielen Seura, 2000)
Dialect boundaries and other boundaries in Finnish Lapland (englanti)2/2000 (104)Harri Mantila (University of Oulu; harri.mantila@oulu.fi)DIALECT BOUNDARIES AND OTHER BOUNDARIES IN FINNISH LAPLAND The article examines the impact of old administrative and functional boundaries on the formation of subgroups amongst the Northern Finnish dialects in Lapland. The writer's main finding is that the most important dialect boundaries in Northern Finland have taken shape as a consequence of two important boundary lines and a meeting of dialects. Firstly, the boundary between the Kemi and Tornio dialects is the same as the boundary that existed between Novgorod and Sweden, the history of which can be traced to as far back as the 12th century. This is also the ancient boundary between Kemi and Tornio Lapland, and is the administrative boundary later confirmed on many occasions. West of this boundary, the region's old Western Finnish dialect features have been best preserved in the Tornio dialect, along with some very archaic features which are no longer found in the Kemi dialects. Correspondingly, the distribution of some dialect features presented as being Karelian features, such as st cluster assimilation and the past tense 3rd person plural het menthin, covers only the area of the Kemi dialect. Toponyms also demonstrate stronger Karelian features along the banks of the River Kemi than the River Tornio.A second major dialect boundary in Northern Finland runs along the southern and western boundaries of Kittil, Sodankyl and Kemijrvi, with the lower reaches of the River Kemijoki forming a separate dialect area. In this area there are features common to Ostrobothnian dialects: the schwa vowel; the representation of the oa or combination in second or later syllables as ua or y; and the single-s inessive case. To the north of the boundary, a thin Saami substrate can be detected in the dialect. This is the boundary of the 17th century parish of Kemi and Kemi Lapland, south of which is concentrated the population that originally ...